2014
DOI: 10.1177/0192623314548765
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Toxicity Studies

Abstract: The field of dermal toxicity continues to evolve in order to accurately predict dermal (and systemic) responses in humans to topically applied chemicals. Although the testing methods have undergone extensive refinements, idiosyncrasies and unexpected issues during the conduct of these studies are not unusual due to the plethora of new vehicles available for formulating test substances, changing regulatory requirements, and introducting new strain and/or species of laboratory animals as no single species or met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Birmingham et al [ 73 ] and Gonipeta et al [ 74 ] sensitized mice to hazelnut and milk whey protein, by transdermal application of the allergen, for 6 consecutive weeks. Although they did not add an adjuvant, they clipped the hair from skin and used mild occlusion for 1 day, which may cause mild inflammatory responses and release DAMPs [ 75 ]. Others [ 54 , 76 ], have used tape stripping methods to promote epicutaneous sensitization to food allergens.…”
Section: Adjuvantsmentioning
confidence: 99%
“…Birmingham et al [ 73 ] and Gonipeta et al [ 74 ] sensitized mice to hazelnut and milk whey protein, by transdermal application of the allergen, for 6 consecutive weeks. Although they did not add an adjuvant, they clipped the hair from skin and used mild occlusion for 1 day, which may cause mild inflammatory responses and release DAMPs [ 75 ]. Others [ 54 , 76 ], have used tape stripping methods to promote epicutaneous sensitization to food allergens.…”
Section: Adjuvantsmentioning
confidence: 99%
“…The parameters evaluated included: mutagenicity, that is, the ability of the substance to cause mutations in the DNA of the organism in which the bioactive is inserted - by severity [ 177 ]; tumorigenicity, which is the ability of the bioactive to cause tumors [ 178 ]; skin irritability, which corresponds to sensitivity that the compound can cause in the skin or in internal organ tissues such as the esophagus, larynx, stomach, and intestine; and toxicity in the reproductive system, which corresponds to the toxic effects that a substance can have on sexual function, and male and female fertility [ 179 , 180 ]. The results are shown in Table 3 [ 181 , 182 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, acute skin irritation and repeated-dose inhalation toxicity was carried out to assess safety of 0.5% of hydrogen peroxide. Skin irritation is considered to be one of the relevant end points of chemicals, and therefore, skin irritation test is critical, if dermal contact is intended (Chandra et al 2015 ). A study on New Zealand rabbits reported that severity of skin irritation increases within the increase in concentration of hydrogen peroxide solution (10% < 35% < 50%).…”
Section: Discussionmentioning
confidence: 99%